Hubungan Pengetahuan Gizi Dan Kepatuhan Diet Terhadap Kadar Kolesterol Total Pada Pasien CHF (Congestive Heart Failure) Di RS Harapan Bunda Bandar Jaya - Vista Citra Sari; Aftulesi Nurhayati; Dera Elva Junita; Mayesti Akhriani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Diet plays a significant role in improving heart function. Excess dietary cholesterol intake can elevate blood cholesterol level, which may lead to vascular narrowing, affect cardiac pumping capacity, and result in Congestive Heart Failure (CHF). Nutritional knowledge influences attitudes and behaviors in food selection, which subsequently affects an individual’s nutritional status. A lack of nutritional knowledge can negatively impact a patient’s compliance with dietary principles and meal planning. This study aimed to analyze the correlation between nutritional knowledge and dietary compliance toward total cholesterol level in CHF patients at Harapan Bunda Hospital of Bandar Jaya. This study employed a cross-sectional design. The population consisted of 180 CHF outpatients from the cardiology clinic, with a sample of 137 respondents determined using the Slovin formula. The research was conducted on November 26, 2024. Data on nutritional knowledge and dietary compliance were collected through questionnaires, while cholesterol level were measured using the Easy Touch GCU device. Data analysis utilized the Gamma correlation test. The study results showed that 58 respondents (42.3%) had moderate nutritional knowledge, 91 respondents (66.4%) adhered to their diets, and 101 respondents (73.7%) had normal cholesterol level. A significant negative correlation was found between nutritional knowledge and cholesterol level (p = 0.001, r = -0.834). Similarly, a significant negative correlation was found between dietary compliance and cholesterol level (p = 0.001, r = -0.938). This indicates that higher level of nutritional knowledge and dietary compliance are associated with lower, more normal cholesterol level.